Evidence of increasing public participation in advance care planning: a comparison of polls in Alberta between 2007 and 2013. Issue 2 (27th January 2016) - Simon, J E; Ghosh, S; Heyland, D; Cooke, T; Davison, S; Holroyd-Leduc, J; Wasylenko, E; Howlett, J; Fassbender, K
Abstract : Background: Advance care planning (ACP) encompasses both verbal and written communications expressing preferences for future health and personal care and helps prepare people for healthcare decision-making in times of medical crisis. Healthcare systems are increasingly promoting ACP as a way to inform medical decision-making, but it is not clear how public engagement in ACP activities is changing over time. Methods: Raw data from 3 independently conducted public polls on ACP engagement, in the same Canadian province, were analysed to assess whether participation in ACP activities changed over 6 years. Results: Statistically significant increases were observed between 2007 and 2013 in: recognising the definition of ACP (54.8% to 80.3%, OR 3.37 (95% CI 2.68 to 4.24)), discussions about healthcare preferences with family (48.4% to 59.8%, OR 1.41 (95% CI 1.17 to 1.69)) and with healthcare providers (9.1% to 17.4%, OR 1.98 (95% CI 1.51 to 2.59)), written ACP plans (21% to 34.6%, OR 1.77 (95% CI 1.45 to 2.17)) and legal documentation (23.4% to 42.7%, OR 2.13 (95% CI 1.75 to 2.59)). These remained significant after adjusting for age, education and self-rated health status. Conclusions: ACP engagement increased over time, although the overall frequency remains low in certain elements such as discussing ACP with healthcare providers. We discuss factors that may be responsible for the increase and provide suggestions for healthcare systems or other public bodies seeking to stimulate engagement in ACP.